Study on preservation of Spirulina maxima - Tram, Tran Bao; Son, Pham Huong; Ngoc Trinh, Bui Thi (Academia Journal of Biology, 2012)
In the 1980s of the past century, the use of immobilized enzymes or cell components for the production of a series of metabolites has become a branch of biotechnology of rapidly growing importance. Up to now, most frequent current uses of immobilize algal cells are applying for different purposes: the production of electricity, hydrogen, ammonia, polysaccharides and glycerol; culture collection handling; the removal of nitrogen and phosphorus; heavy metal removal/recovery. Immobilization techniques can be primarily divided into two groups: ‘passive” and “active” immobilization with various matrices: polyurethane foam, polyvinyl foam, glass beads, agar, alginate, agarose, carrageenan, chitosan.... Spirulina has been widely used in food, farmaceutical and cosmetic industries. The aim of our work was to find out preservation for S. maxima. In this report we carried out immobilizing of S. maxima in gel solution at 2, 3, 4% (w/v) concentrations. The growth responses of immobilized and normal agar culture of S. maxima were compared. The effect of temperature and time of the storage on growth of S. maxima was reviewed, too. The results showed that S. maxima can be maintained by both of immobilized and agar stock, but the recovered ability of immobilized S. maxima in gel was better than on agar stock after 6 months of preservation. We also found out that the preservation in concentration of 3% gel, at 5oC was the best condition for long-term storage of S. maxima. The presevation of S. maxima by immobilization technique is quite easy method and it help contributing to the extension of term for storage, reducing contaminations and keeping the strain intact with high quality